设数列{an}满足:a1=1,an+1=
(1)求a2,a3; (2)令bn=
(3)已知f(n)=6an+1-3an,求证:f(1)•f(2)…f(n)>
|
(1)∵数列{an}满足:a1=1,an+1=
(1+4an+1 16
)(n∈N*),1+24an
∴a2=
(1+4a1+1 16
)=1+24a1
,5 8
a3=
(1+4a2+1 16
)=1+24a2
(1+4×1 16
+5 8
)=1+24× 5 8
.15 32
(2)∵bn=
,∴an= 1+24an
,代入 an+1=bn2-1 24
(1+4an+1 16
)(n∈N*) 得 1+24an
=bn+12-1 24
(1+4× 1 16
+ bn),化简可得 4bn+12=(bn+3)2,即 2bn+1=bn+3.bn2-1 24
∴2(bn+1-3)=bn-3,∴{bn-3}是以2为首项,以
为公比的等比数列,1 2
∴bn-3=2(
)n-1,∴bn=(1 2
)n-2+3.1 2
(3)证明:∵已知 an=
=bn2-1 24
=(
)n-2+9 + 6×(1 4
)n-2-11 2 24
×(2 3
)n+(1 4
)n+1 2
,1 3
故 f(n)=6an+1-3an =6[
×(2 3
)n+1+(1 4
)n+1+1 2
]-3(1 3
×(2 3
)n+(1 4
)n+1 2
)=1-1 3 1 4n
=(1-
)(1+1 2n
).1 2n
当n≥2时,有(1+
)•(1-1 2n-1
)=1-1 2n
+1 2n
-1 2n-1
=1+1 22n-1
>1.2n-1-1 22n-1
∴f(1)•f(2)…•f(n)=(1-
)(1+1 2
)•(1-1 2
)(1+1 4
)…(1-1 4
)(1+1 2n
)1 2n
>(1-
)(1+1 2
)=1 2n
+1 2
>1 2n+1
.1 2
故要证的不等式 f(1)•f(2)…f(n)>
成立.1 2